Chemical Characteristics of Biodegradable Packaging Made from Whey and Oil Palm Empty Fruit Bunch Juice - Adriansyah, Muhammad; Syahputra, Zaky; Fauzi, Arkan; Juliyarsi, Indri (Faculty of Animal Science Universitas Brawijaya, 2024)
Biodegradable packaging is a coating made from edible materials that act as a barrier to moisture, oxygen, and solutes in food. Biodegradable packaging is made from renewable materials such as starch, cellulose, and protein. Cheese whey is a protein source that can be used as a biodegradable material. In contrast, a starch source that can be utilized as a base material for biodegradable packaging is oil palm empty fruit bunches. This study aimed to determine chemical and physical change and also the properties of biodegradable packaging due to the addition of palm empty fruit bunch starch juice. The research design used was a completely randomized design with four treatments, namely without palm oil empty bunch juice (control) = A and with the addition of 0.75% = B, 1% = C, and 1.25% = D. The research results showed that the addition of empty oil palm bunch juice had a significant effect (p < 0.05) on thickness, water content and water vapor transmission, in the solubility and degradability tests the addition of empty oil palm bunch juice showed no significant effect (p > 0.05). The lowest thickness analysis result was 0.1420 mm; the lowest moisture content was 25.27%; the lowest water vapor transmission was 5.178 g/m2/day; the lowest solubility was 55.62%. All samples were composed entirely on the 7th day and 100% decomposed in the soil. The results of the test showed that the best treatment was found in the sample with the addition of 1.25% juice.